Empowering novice academics for student success : wearing different hats - Hugo, J. (Johann), 1954- (SUN MeDIA, 2021)
This book is essential for academics that enter the field of higher education and training, as it focuses on preparing teachers and trainers to respond appropriately to student success challenges.